God gave us two - Bergren, Lisa Tawn.; Bryant, Laura J. (Euless, TX : Waterbrook Press, 2001)
Little Cub has questions about the new baby that Mama is expecting, but she learns that babies are gifts from God.
Keywords: Infants -- Fiction; Brothers and sisters -- Fiction; Polar bear -- Fiction; Bears -- Fiction; Christian life -- Fiction